PENGARUH SENAM TAI CHI TERHADAP TEKANAN DARAH PADA LANSIA DI KOTA BANDUNG - Fauziah, Liliek; Juliyanti, Juliyanti; Sari, Claudia Novita (Jurnal Sehat Masada, 2025)
Hypertension is a degenerative disease that often occurs in the elderly, treatment that can be done to stabilize blood pressure can be done by using complementary therapy: Tai Chi gymnastics, regular movements and breathing in Tai Chi gymnastics have the potential to lower blood pressure. The purpose of this study was to determine whether there is an effect of complementary therapy: Tai Chi gymnastics on blood pressure in hypertensive elderly in the Tai Chi gymnastics community. The design of this study uses quantitative research in an experimental design with a design pretestposttest with control group. The sampling technique used total sampling technique with 62 respondents divided into 2 groups, namely 31 elderly people with hypertension in the intervention group in the Tai Chi gymnastics community and 31 elderly people in the control group in Pajajaran Village RW 03. The data processed using the testmann-whitney uThe results of this study show that before Tai Chi exercise, the elderly experienced hypertension 1 as much as 87.1% and after Tai Chi exercise, the elderly with high normal blood pressure were as much as 54.8%. Results mann-whitney uobtained p value 0.00 (p <0.05) which shows there is a difference in blood pressure in elderly hypertensive who follow Tai Chi gymnastics and do not follow Tai Chi gymnastics in Bandung City. Based on this study, it is expected to be a reference material in improving health promotion for elderly with hypertension.